Gambaran Pola Asuh Orang Tua Terhadap Balita Stunting di Lingkungan Puskesmas Pekauman - Syahdariantie*, Hellda; Aprianty, Rizqi Amalia; Arpandy, Ghea Amalia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Stunting is a condition of failure to develop in children which can affect brain development, physical growth, and intelligence in children. This reseach aims to describe parenting styles for stunting toddlers in the Pekauman Health Center. The method used in this study is descriptive qualitative with a phenomenological approach. The subjects in this reseach were 2 pairs of parents as the main informants and 1 nutrition worker (TPG) at the Pekauman Health Center as a significant other. The result of stunting can occur because of negligent parenting in health practices, feeding, sanitation, interactions between parents and children, practices of preparing, processing and serving food to children, as well as paying attention to the growth and development of toddlers so that impact on the nutritional status of children under five according to BB/U and TB/U.